A problem-based approach to teaching research methodology to medical graduates in Iran - Hosseini, Mehrdad Jalalian; Bazargni, Reyhaneh; Abd Latiff, Latiffah; Syed Hassan, Syed Tajuddin; Hanachi, Parichehr; Othman, Mohamed (Australasian Medical Journal, 2009)
Physicians are reticent to participate in research projects for a variety of reasons. Facilitating the active involvement of doctors in research projects is a high priority for the Iranian Blood Transfusion Organization (IBTO). A one-month training course on research methodology was conducted for a group of physicians in Mashhad, in northeast Iran. The participants were divided in ten groups. They prepared a research proposal under the guidance of a workshop leader. The quality of the research proposals, which were prepared by all participants, went beyond our expectations. All of the research proposals were relevant to blood safety. In this brief report we describe our approach.